Distinguishing hypertrophic cardiomyopathy from athlete`s heart physiological remodelling: clinical significance, diagnostic strategies and implications for preparticipation screening - Maron, B. J. (British Journal of Sports Medicine, 2009)
Sudden cardiac death in young competitive athletes is an important public health problem, although a relatively low-event-rate phenomenon. The single most common cardiovascular cause of these unexpected catastrophes is hypertrophic cardiomyopathy (HCM), accounting for about one-third of cases. Since the phenotypic expression of HCM is variable, and not uncommonly includes patients with mild and localised left ventricular hypertrophy, the differential diagnosis with physiological remodelling of athlete`s heart not uncommonly arises. This review discusses those non-invasive strategies that are useful in distinguishing the benign consequences of systematic athletic training from pathological left ventricular hypertrophy with the potential for sudden cardiac death. Preparticipation screening in healthy general athlete populations may raise the suspicion of HCM, and ultimately lead to definitive diagnosis. However, recently controversy has arisen regarding the most effective and practical strategy for the screening of athletes. European investigators have promoted routine 12-lead ECGs as part of a national mandatory programme distinct from the customary practice in the US which is limited to history and physical examinations. Consensus criteria and recommendations for eligibility and disqualification of athletes with HCM (and other cardiovascular abnormalities) have proved useful to the practising community.